Philosophical Foundations of Human Rights - Miró Quesada Cantuarias, Francisco (1982)
This article focuses its analysis on the rational nature of philosophy and its importance in the understanding and justifying human rights. In this context, the author discusses the search for definitive solutions in philosophy, its distinction from science, and the role of evidence and logical deduction in knowledge foundation. He also addresses the complexity of normative and propositional evidence and their implications for the human rights grounding . The article continues with an examination on this topic, and distinguishes between absolute and relative grounding. Given that an absolute grounding is unlikely due to the less universal nature of normative evidence, as opposed to propositional evidence, it proposes a relative grounding, based on the hypothesis of rational behavior, where respect for freedom and rights arises from the necessity of non-arbitrary behavior in society. Finally, the article concludes that a rational approach to human rights is compelling and crucial for harmonious social coexistence, although it is challenging to achieve an absolute foundation.